Karta zapadnago berega Novoĭ Zemli otʺ mysa Sukhoĭ Nos do mysa Si︠e︡vernyĭ Gusinyĭ Nos sostavlena sʺ Russkikhʺ opiseĭ 1821-1901 g.g. na osnovanīi astronomicheskikhʺ punktovʺ : Kapit. Litke 1823 g. Prof. Nordenshilʹda 1875-1876 g.g. Astron. Fussa 1882 g. Porch. Astafʹeva 1889 g. i Leĭten. Zhdanko 1893 i 1895 g. g. Izdana Glavnymʺ Gidrograficheskimʺ Upravlenīemʺ Morskogo Ministerstva vʺ 1902 godu / Kopiroval khimicheskoi︠u︡ K. Fedorovʺ - Russia. Glavnoe gidrograficheskoe upravlenīe ([Санкт-Петрбург] : Морское министерство, Главное гидрографическое управленіе; Sankt-Petrburg : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe, 1902)
Relief shown by form lines. Depths shown by soundings.; Top margin title translation: Arctic Ocean, western coast of Novaya Zemlya.; Title translation: Map of the western coast of Novaya Zemlya from Cape Sukhoi Nos to Cape Northern Gusinyi Nos from the Russian surveys of 1821-1901 based on the astronomical points of Captain Litke 1823, Professor Nordenskiöld 1875-1876, Astronomer Fuss 1882, Lieutenant Astafev 1889, and Lieutenant Zhdanko 1893 and 1895. Published by the Main Hydrographic Office of Admirality in 1902.; Greenwich and Pulkovo meridians given.; Includes two illustrations of the coast line.; "Masshtabʺ 3 mili vʺ di︠u︡ĭmi︠e︡ (1/219240)" = Scale 3 miles in 1 inch (1/219240).; "No. 583" -- margins Color; 1:219,240